Interactions between maternal effects and dispersal - Mike Fowler (Oikos, 2005)
Maternal effects and spatial processes are rightly recognised as being of great importance in the life histories of a number of different organisms. Previously, little effort has been made for investigating the potential for changes to arise from interactions between these two crucial processes. Here I tested the outcome of introducing a maternal effect on a population of dispersing organisms in different ways, under both spatially homogeneous and heterogeneous conditions, through novel modification of a well-known population model. First, I proposed that parents contribute a proportion of offspring based on their own developmental experience. This is applied to dispersing organisms as well as those that remain in their natal patch to breed. I go on to ask how the density of dispersing offspring might be influenced by a maternal effect. What happens if parents that developed under relatively good (or bad) conditions compared to current conditions invest in dispersing offspring? This relaxes the assumption that populations have perfect knowledge of the local carrying capacity. The results highlight an interesting range of outcomes. By introducing a maternal effect into the potential future reproductive output otherwise highly unstable population dynamics were simplified (but not stabilised). If maternal effects affect dispersal decisions, it is possible for regular cycles with a period consistent with many examples from ecological time-series’ to arise. These results are in agreement with previous studies, however, by investigating the effects in different aspects of life history, it is possible to predict the direction of the impact on population dynamics. This work also highlights the potential for regular cycles in population dynamics to arise due to maternal effects, in agreement with recent field studies.